Grasping the Interplay between the Verbal Cultural Diversity and Critical Thinking, and Their Consequences for African American Education - Crogman, Horace (Frontiers in Education, 2017)
The role language has in human learning has been discussed in the context of its impact on culture through African American communities. A strong link between thinking and language through the framework of question asking was reported. This essay improves upon Crogman and Trebeau’s (2016) Generated Question Learning Model by incorporating language and comprehension as major tenets. The proposed argument is centered on language as the determinant of structured thinking, which in essence brings about learning through sensory experience. Further, the case was made for issues that may emerge in learning when the cultural norms of the learner are ignored.